2010
DOI: 10.1098/rsbl.2009.0909
|View full text |Cite
|
Sign up to set email alerts
|

Group provisioning limits sharing conflict among nestlings in joint-nesting Taiwan yuhinas

Abstract: Offspring often compete over limited available resources. Such sibling competition may be detrimental to parents both because it entails wasted expenditure and because it allows stronger offspring to obtain a disproportionate share of resources. We studied nestling conflict over food and its resolution in a joint-nesting species of bird, the Taiwan yuhina (Yuhina brunneiceps). We show that adult yuhinas coordinate their feeding visits, and that this coordination limits competition among nestlings, leading to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 11 publications
2
44
0
Order By: Relevance
“…Pair synchrony, and therefore the equity in partners' work rate, increased rather than decreased with experimental brood size, which suggests that partners coped with additional offspring demand by increasing cooperation rather than intensifying sexual conflict. This pattern is also consistent with the hypotheses that nest visit synchrony is an adaptive response to counter offspring competition (Shen et al 2010), nest predation risk (Raihani et al 2010), or to improve the assessment of other individuals' care (Doutrelant and Covas 2007;McDonald et al 2008), as suggested for cooperative breeders. Accordingly, even though nest visit synchrony followed foraging synchrony, it also responded directly to the brood size manipulation, unlike the response to nestling age, which was mostly driven by synchrony while foraging.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Pair synchrony, and therefore the equity in partners' work rate, increased rather than decreased with experimental brood size, which suggests that partners coped with additional offspring demand by increasing cooperation rather than intensifying sexual conflict. This pattern is also consistent with the hypotheses that nest visit synchrony is an adaptive response to counter offspring competition (Shen et al 2010), nest predation risk (Raihani et al 2010), or to improve the assessment of other individuals' care (Doutrelant and Covas 2007;McDonald et al 2008), as suggested for cooperative breeders. Accordingly, even though nest visit synchrony followed foraging synchrony, it also responded directly to the brood size manipulation, unlike the response to nestling age, which was mostly driven by synchrony while foraging.…”
Section: Discussionsupporting
confidence: 83%
“…"Experimental brood size" was the number of nestlings in the nest after manipulation, whereas "brood manipulation" was the deviation from the original brood size calculated as (postexperimental brood size -original brood size)/original brood size. Food partitioning was computed as in Shen et al (2010) using the "skew index S," which varies from 0 to 1, for increasing inequality among nestlings. For the between-pair comparison, parental behavior and seed count were standardized per brood size by using the residuals of their linear regression with experimental brood size.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of recorded video can vary depending on the scale of the experiment. For example, a study by Shen et al (2010) examining provisioning in Taiwan Yuhinas (Yuhina brunneiceps) analyzed 122 h of video, while Gladbach et al (2009) analyzed 720 h of Wilson's Storm Petrel (Oceanites oceanicus) video. Analyzing this amount of video is arduous and also has a high potential for error due to observer fatigue.…”
Section: Introductionmentioning
confidence: 99%